Peso e ECC adequados não são suficientes para estimular a puberdade se novilhas até 18 meses - LIMA, Thais Ferreira; DA SILVA, Aldair Felix; STERZA, Fabiana de Andrade Melo; FERREIRA, Mariane Gabriela Cesar Ribeiro; DOS SANTOS, Aracy Garcia Travassos; SANTOS, Caroliny Silva (ANAIS DO ENIC, 2024)
-